Trend 1976 - 1996. Statistics Canada. CANSIM: Information and Communications Technology - Telecommunications Industries | Country: Canada | Province: Newfoundland and Labrador | Table: Telephone statistics | Variable: Local service revenue | Units: $CAD x 1,000, 1976-1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-128. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Information and Communications Technology - Telecommunications Industries | Country: Canada | Province: Newfoundland and Labrador | Table: Telephone statistics | Variable: Local service revenue | Units: $CAD x 1,000, 1976-1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-128. Dataset: Presents statistics on the revenues, expenses, employment, and use of the networks of telecommunications services and related industries. These industries include providers of fixed and mobile telephony, Internet access, satellite access, and similar services. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Telecommunications Services, Information and Communications Technology, Internet Access, Telecommunications, Telecommunications Industry, Internet Use